Gambaran Pengetahuan tentang Pentingnya Vaksin Meningitis pada Jemaah Umroh di KKP Kelas III Jambi - Basra, Yosi (Indonesian Journal of Health Community, 2023)
Public interest in Umrah worship is currently increasing. The dense number of Umrah pilgrims poses a risk of disease transmission, especially those from endemic areas such as meningitis. This study aims to describe the knowledge about the importance of the meningitis vaccine in Umrah pilgrims. This research is a quantitative research with a descriptive research design. This research was conducted at the Class III Jambi MPA in November - December 2022. The population in this study were all Umrah pilgrims who would vaccinate against meningitis and sampling was carried out using a total sampling technique with a total of 132 people. Data collection was carried out using a questionnaire and the results were analyzed univariately. The results of the univariate analysis showed that there were 67 (50.8%) respondents who had good knowledge about the importance of the meningitis vaccine, there were 45 (34.1%) respondents who had poor knowledge about the timeliness of giving the meningitis vaccine, there were 62 (47.0%) ) respondents had good knowledge about the benefits of the meningitis vaccine and there were 75 (56.8%) respondents who had poor knowledge about the contraindications for administering the meningitis vaccine to Umrah pilgrims.